Maximum smoke temperature in the longitudinally ventilated tunnel fire: Influence of the separating distance between two sources. (January 2021) - Ma, Xin; Luo, Shengfeng; Fang, Tingyong; Wang, Jingwei; Wan, Lulu
Highlights: The smoke temperature at upstream fire strongly depends on the downstream fire. Maximum smoke temperature was corrected, considering effects of two fire sources. Maximum smoke temperature in tunnel fire with two fire sources could be predicted. Abstract: The maximum smoke temperature is a critical parameter of tunnel fire. Previous work on this subject has studied the cases with a single fire source. In this study, maximum smoke temperature for cases with two fire sources is discussed through reduced-scale experiments and theoretical analysis. The relationship between the separating distance of dual-source fire and the maximum temperature under longitudinal wind conditions was determined. A correction factor was proposed to characterize the effect of the distance between the dual fire sources on the maximum smoke temperature. The results indicated that the maximum temperature beneath the ceiling at the upstream fire source strongly related to the downstream fire source, for the cases with a small separating distance of the dual-source fire. The influence of downstream fire on the upstream fire source gradually weakens as the separating distance increases. An exponential factor about the distance of the dual-source fire was applied to correct the maximum smoke temperature. The predicted results based on the revised model agree well with the experiment.